1999
DOI: 10.1074/jbc.274.49.34758
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian TOR Controls One of Two Kinase Pathways Acting upon nPKCδ and nPKCε

Abstract: There are three conserved phosphorylation sites in protein kinase C (PKC) isotypes that have been termed priming sites and play an important role in PKC function. The requirements and pathways involved in novel (nPKC) phosphorylation have been investigated here. The evidence presented for nPKC␦ shows that there are two independent kinase pathways that act upon the activation loop (Thr-505) and a C-terminal hydrophobic site (Ser-662) and that the phosphorylation of the Ser-662 site is protected from dephosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
156
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(170 citation statements)
references
References 39 publications
11
156
3
Order By: Relevance
“…PKC is normally coupled to the IL-2R through PI 3 K, as PKC is activated by PDK1-dependent phosphorylation (40), and a role for PKC in IL-2-mediated signal transduction has been defined using the IL-2-dependent cell line CTLL (59,60). Interestingly, full activation of the PKC-␦ isoform requires the activity of mTOR/FRAP (61), which is in turn dependent on PKB/Akt (62). These two distinct PI 3 K-dependent pathways leading to PKC activation, which can be bypassed using phorbol esters, represent a set of biochemical events that could potentially be defective in the undivided pool.…”
Section: Discussionmentioning
confidence: 99%
“…PKC is normally coupled to the IL-2R through PI 3 K, as PKC is activated by PDK1-dependent phosphorylation (40), and a role for PKC in IL-2-mediated signal transduction has been defined using the IL-2-dependent cell line CTLL (59,60). Interestingly, full activation of the PKC-␦ isoform requires the activity of mTOR/FRAP (61), which is in turn dependent on PKB/Akt (62). These two distinct PI 3 K-dependent pathways leading to PKC activation, which can be bypassed using phorbol esters, represent a set of biochemical events that could potentially be defective in the undivided pool.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that other signalling pathways or autophosphorylation may regulate these isoforms at this site. Indeed, the TM of PKC has been reported to be an autophosphorylation site [54,66]. While deletion of mTORC2-specific components in MEFs appears to have no effect on TM phosphorylation or expression of PKC , this pathway regulates TM phosphorylation of PKC in T lymphocytes [61].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This theme developed because it was demonstrated that PKCs (predominantly cPKCs) are phosphorylated at these sites shortly after synthesis [83,42] and are often highly phosphorylated at these sites in many types of cells grown in culture, even under quiescent conditions [26,66,84]. In the absence of phosphorylation at one or more of these sites, catalytic activation of these isoforms is impaired or enzyme stability is compromised.…”
Section: Pkc Phosphorylation: Constitutive or Inducible?mentioning
confidence: 99%
See 1 more Smart Citation
“…PDK1 can also directly phosphorylate the activation loop of other AGC kinases that undergo phosphorylation by mTOR at their hydrophobic motifs (e.g., PKCa, PKCd, S6K). 38,39,[76][77][78] Therefore, the PI3K=PDK1 pathway can activate AGC kinases independently of TSC2 or Rheb. The concurrent phosphorylation of AGC kinases by PDK1 and mTOR may be required for their maximal activation or stability.…”
Section: Regulated Mtorc-protein Interactionsmentioning
confidence: 99%